2011
DOI: 10.1111/j.1461-0248.2011.01718.x
|View full text |Cite
|
Sign up to set email alerts
|

Toxin‐assisted micropredation: experimental evidence shows that contact micropredation rather than exotoxicity is the role of Prymnesium toxins

Abstract: Blooms of Prymnesium parvum can severely harm fish and zooplankton, presumably through the release of allelopathic exotoxins that offer advantages for Prymnesium in its interactions with competitors and prey. We show that Prymnesium attaches to zooplankton and fish, causing mortality, whereas exposure of these organisms to Prymnesium across a permeable membrane does not cause mortality. We also show that Prymnesium exotoxins are released independently of contact toxicity only in response to experimental proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 48 publications
3
44
0
Order By: Relevance
“…However, recent studies hypothesize that the majority of Prymnesium toxicity is cellular-based rather than related to exotoxins production (Remmel et al 2011). Further, reduction of A. franciscana movement with exposure time, as shown in the present study at the maximum exposure concentration of P. parvum, is in accordance with the results of Remmel and Hambright (2012). These investigators observed that Prymensium cells were attached to most exterior surfaces, to fish gills and to feeding and respiratory appendages in zooplankton, which contributed to the movement depletion of individuals.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, recent studies hypothesize that the majority of Prymnesium toxicity is cellular-based rather than related to exotoxins production (Remmel et al 2011). Further, reduction of A. franciscana movement with exposure time, as shown in the present study at the maximum exposure concentration of P. parvum, is in accordance with the results of Remmel and Hambright (2012). These investigators observed that Prymensium cells were attached to most exterior surfaces, to fish gills and to feeding and respiratory appendages in zooplankton, which contributed to the movement depletion of individuals.…”
Section: Discussionsupporting
confidence: 80%
“…These effective concentrations are within the range of those calculated by Hansen et al (2003), who reported a cell division reduction of newly-fertilizing eggs of the sea urchin Sphaerechinus granularis exposed to a haptophyte. However, Remmel and Hambright (2012) suggested that the presence of toxins in the filtrate could be an artefact caused by the vacuum pressure used in the filtration process, which can cause cell disruption and the subsequent release of intracellular toxins. The result of the filtrate reported in the present study should therefore be considered carefully.…”
Section: Discussionmentioning
confidence: 99%
“…In the laboratory, P. parvum tends to have higher toxicity when grown in N-or P-deficient conditions, i.e., unbalanced N∶P (Granéli et al 2012). Ambient environmental conditions during blooms of P. parvum generally corroborate these findings of stress-induced toxicity, i.e., blooms tend to occur under low N∶P availability (Aure and Rey 1992, Bales et al 1993, and researchers have hypothesized that the evolutionary benefit of toxigenesis is likely to be related to nutrient acquisition (Lewis 1986, Beszteri et al 2012, Remmel and Hambright 2012, Driscoll et al 2013). The need for nutrient acquisition would generally signal unfavorable, hence stressful, conditions for growth.…”
mentioning
confidence: 62%
“…This apparent paradox has led to speculation that its toxigenic capabilities provide a competitive edge to P. parvum over other algae, allowing blooms to develop during periods of stress, such as created by low nutrient availabilities (for a review, see Granéli et al, 2012). However, while toxicity may have important roles in predator avoidance and heterotrophy in this unicellular mixotroph, toxin production is unlikely to provide a competitive advantage to P. parvum to the degree necessary to lead to bloom formation under suboptimal environmental conditions (Jonsson et al, 2009;Remmel and Hambright, 2012).…”
Section: Introductionmentioning
confidence: 99%